2002
DOI: 10.1074/jbc.m200702200
|View full text |Cite
|
Sign up to set email alerts
|

Expression of l-Histidine Decarboxylase in Mouse Male Germ Cells

Abstract: Histamine synthesis in male reproductive tissues remains largely unknown. The interaction between stem cell factor and its receptor, c-Kit, has been found to be essential for the maturation of male germ cells and peripheral mast cells. Based on this analogy, we investigated the expression of histidine decarboxylase (HDC), the rate-limiting enzyme of histamine synthesis, in mouse male germ cells. Immunohistochemical analyses revealed that HDC is localized in the acrosomes of spermatids and spermatozoa. In the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
3

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 26 publications
1
19
0
3
Order By: Relevance
“…Unlike with tumor tissue, we found that both the 54-and 74-kDa histidine decarboxylases are equally represented in all three colon cancer cell lines. Because multiple forms of histidine decarboxylase have been shown to be generated by tissue-or cell-specific posttranslational processing (42,44), it might be hypothesized that different processing pathways are responsible for the different expression of the 54-kDa subunit form in either the tumor tissue or the colon cancer cell lines. Our study showed that high levels of histidine decarboxylase activity and histamine content were correlated with the presence of lymph node and/or distant metastases in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike with tumor tissue, we found that both the 54-and 74-kDa histidine decarboxylases are equally represented in all three colon cancer cell lines. Because multiple forms of histidine decarboxylase have been shown to be generated by tissue-or cell-specific posttranslational processing (42,44), it might be hypothesized that different processing pathways are responsible for the different expression of the 54-kDa subunit form in either the tumor tissue or the colon cancer cell lines. Our study showed that high levels of histidine decarboxylase activity and histamine content were correlated with the presence of lymph node and/or distant metastases in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, only 74-kDa form was detected in lipopolysaccharide-activated mouse macrophages and monomeric IgE-activated immature bone marrow-derived cultured mast cells, in both of which a large increase in histamine synthesis is observed (21,22). Other variants with intermediate sizes (58ϳ64-kDa) have also been reported in the stomach, fetal liver, and testis (18,23,24). These findings have highlighted the complexity in the regulation of enzyme activity and intracellular localization of HDC through the post-translational processing.…”
mentioning
confidence: 93%
“…Total RNA was extracted from the BMMCs, and first-strand cDNA was generated from 1 µg of RNA by using oligo (dT) [12][13][14][15][16][17][18] primer and SuperScriptIII RNase H Reverse Transcriptase (Invitrogen) according to the manufacturer's protocol. The reaction mixture was amplified with the oligonucleotides specific for HDC, MMCP-1, MMCP-2, MMCP-4 and β-actin (11-13).…”
Section: Rna Isolation and Rt-pcr Analysismentioning
confidence: 99%